Identification and Prioritization of Solutions for Handling of Administrative Violations Time Reduction among Medical Universities Staff and Their Subsidiary Organizations - Serajeddin Grey; Abolfazl Rouzbeh; Bahman Khosravi; Farhad Habibi Nodeh; Arezo Rahbari; Hosein Safari (Tehran University of Medical Sciences, 2018)
Background: Administrative violations of employees at their workplace create a conflict between individual and organizational goals. Due to the long process of handling these violations, this study aimed to identify and present some suitable solutions in order to reduce delay in the health sector.   Materials and Methods: This study was carried out at three steps. At the first step, causes of delay in handling of administrative violations were extracted along with the proposed solutions using interviews. In second step, Delphi method was applied in order to find out the agreement of experts on the suggested solutions. In third step, practical solutions were prioritized using the analytic hierarchy process.   Results: Overall, 23 out of 39 solutions were certified  after consultation with experts running the first round of Delphi using the interview. These solutions were presented to 15 experts using a self-constructed questionnaire and 18 solutions were approved by the experts finally.Solutions were divided into six groups of motivational, organizational, administrative, process, and research group solutions.   Conclusion: Training as the main key to prevent the delay can work effectively at all levels and processes of service delivery. Hiring well-informed and conscious managers at various organizational levels as well as having experienced and mindful research group on administrative violations can speed up the process of handling these violations.